STRATEGI MENCIPTAKAN KEBERLANJUTAN UMKM GITAR, DI NGROMBO, BAKI, SUKOHARJO - Istiatin Istiatin; Burhanudin Ahmad Yani (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
This study aims to analyze in detail the characteristics of the owner, the characteristics of the UMKM towards the transformation and success of the UMKM Guitar business in Ngrombo, Baki, Sukoharjo. Examine the transformation of the sustainability of the guitar business in the village of Ngrombo, Baki, Sukoharjo. The study discusses the success of the UMKM Guitar by looking at the supporting factors of the characteristics of the owner and the characteristics of the business with the supporting factors by doing transformations.The method in this research uses descriptive quantitative design. While the entire population of guitar SMEs in the Ngrombo, Baki, Sukoharjo. Samples used by guitar SMEs that have been operating for more than 5 years, amounting to 39 entrepreneurs who subsequently as research respondents. Data collection techniques by distributing questionnaires to 39 guitar entrepreneurs in accordance with the description of the respondent. The results of the questionnaire were then processed with PLSThe results showed the Characteristics of Owners influence positively and significantly on the Transformations carried out by business actors. The transformation in question is the willingness to change and advance the success of its business and ultimately its sustainability. The characteristics of SMEs do not significantly influence this transformation because they are based on experience in running their businesses. This research resulted in Business Transformation, Owner Characteristics and Characteristics of SMEs influencing business sustainability.